AAV9-mediated gene transfer of desmin ameliorates cardiomyopathy in desmin-deficient mice - Heckmann, Markus B.; Bauer, Ralf; Jungmann, Andreas; Rapti, Kleopatra; Katus, Hugo; Müller, Oliver J. (Gene therapy, 2016)
Mutations of the human desmin (DES) gene cause autosomal dominant and recessive myopathies affecting skeletal and cardiac muscle tissue. Desmin knockout mice (DES-KO), which develop progressive myopathy and cardiomyopathy, mirror rare human recessive desminopathies in which mutations on both DES alleles lead to a complete ablation of desmin protein expression. Here, we investigated whether an adeno-associated virus-mediated gene transfer of wild-type desmin cDNA (AAV-DES) attenuates cardiomyopathy in these mice. Our approach leads to a partial reconstitution of desmin protein expression and the de novo formation of the extrasarcomeric desmin-syncoilin network in cardiomyocytes of treated animals. This finding was accompanied by reduced fibrosis and heart weights and improved systolic left-ventricular function when compared with control vector-treated DES-KO mice. Since the re-expression of desmin protein in cardiomyocytes of DES-KO mice restores the extrasarcomeric desmin-syncoilin cytoskeleton, attenuates the degree of cardiac hypertrophy and fibrosis, and improves contractile function, AAV-mediated desmin gene transfer may be a novel and promising therapeutic approach for patients with cardiomyopathy due to the complete lack of desmin protein expression.